High‐dimensional single‐cell proteomics analysis identifies immune checkpoint signatures and therapeutic targets in ulcerative colitis. Issue 3 (9th January 2019) - Fuchs, Sebastian; Sawas, Nadia; Staedler, Nicolas; Schubert, David A.; D'Andrea, Annalisa; Zeiser, Robert; Piali, Luca; Hruz, Petr; Frei, Andreas P.
Abstract: Immune checkpoints are regulators of immune cells and play key roles in the modulation of immune responses. The role of checkpoints in autoimmune disease is poorly understood but likely to be central since checkpoint inhibition during cancer treatment can cause autoimmunity. We generated a high‐dimensional single‐cell proteomics data set from PBMCs of healthy individuals and patients with ulcerative colitis (UC) by mass cytometry, enabling systems‐wide analyses of immune cell frequencies and cell type‐specific expression patterns of 12 immune checkpoints. Subtle but significant changes in immune cell frequencies and checkpoint expression were observed between UC patients on different treatment regimens and between patients and healthy controls. Most strikingly, UC patients showed a reduced number of peripheral NK‐cells and those cells showed an altered phenotype including increased TIGIT expression. Based on these results, we modulated NK‐cell function ex vivo through targeting of TIGIT pathway members. In summary, we describe a pattern of changes in immune cell abundance and checkpoint expression as a basis for UC patient stratification and we show modulation of a corresponding immune cell subset through checkpoint targeting. Our approach can be used for the identification of pathogenic immune cell subsets and guide target selection in autoimmunity and chronic inflammation. Abstract : High‐dimensional single‐cell proteomics identifies treatment‐specific patterns of immune cell type frequencies and immune checkpoint expression in peripheral blood of patients with ulcerative colitis. Phenotypic changes observed in the peripheral NK cell compartment possibly reflect the inflammatory state in the gut tissue and corresponding cells can be modulated through checkpoint targeting.